Palladium-Loaded Hierarchical Flower-like Tin Dioxide Structure as Chemosensor Exhibiting High Ethanol Response in Humid Conditions - Zito, Cecilia A. [UNESP]; Perfecto, Tarcísio M. [UNESP]; Volanti, Diogo P. [UNESP] (Wiley, 2017)
The impact of humidity is a crucial factor in the sensing performance of a chemiresistive gas sensor. Therefore, strategies for developing sensors with a small humidity dependence are required. Herein, the volatile organic compound (VOC)-sensing performance of palladium-loaded hierarchical flower-like tin dioxide structures (Pd/FL-SnO2) under humid conditions is reported. To prepare the Pd/FL-SnO2 heterostructures, FL-SnO2 is first synthesized using a microwave-assisted solvothermal method, followed by calcination, and then is loaded with Pd nanoparticles (NPs). VOC-sensing studies are conducted in dry and wet air with relative humidities (RHs) between 25% and 98%. FL-SnO2 and Pd/FL-SnO2 exhibit an enhanced response toward ethanol in comparison with other VOCs, including acetone, benzene, methanol, m-xylene, and toluene. However, FL-SnO2 with Pd NPs has a substantially decreased optimal working temperature, from 340 to 140 °C, and an improved selectivity. Furthermore, the ethanol response of the Pd/FL-SnO2 heterostructures is preserved under humid conditions, whereas the response of FL-SnO2 is significantly affected by humidity. The response to 100 ppm of ethanol under 98% RH is 3.1 and 8.0 for neat FL-SnO2 and 5% Pd/FL-SnO2 heterostructure, respectively. The ethanol-sensing performance enhancement under high humidity is attributed to the Pd/SnO2 heterointerface.
Keywords: humidity interference; nanostructured architectures; Pd-decorated; SnO2